The Effect of Fraze Mowing on Overseed Establishment in Cynodon dactylon Turf. Issue 1 (19th October 2017) - Munshaw, G. C.; Dickson, K. H.; Cropper, K. L.; Sorochan, J. C.
Abstract : Cynodon spp. (bermudagrass) golf courses and athletic fields in warm‐humid and warm‐arid regions are often annually overseeded with a cool‐season grass to improve turf performance during autumn and winter. Previous research has shown that preplant cultivation treatments to the C. dactylon base typically results in improved overseed establishment. Fraze mowing is a relatively new turf maintenance technique in which thatch and grass verdure is aggressively removed by blades attached to a revolving rotor. Because fraze mowers can significantly reduce C. dactylon competition for the overseed, a study was devised to determine the effectiveness of fraze mowing as a preplant technique prior to overseeding. The study was conducted in Lexington, KY, and Knoxville, TN, during the fall and winter of 2015–2016. Treatments were applied on 17 September and consisted of an untreated control, vertical mowing (one direction, 7.5 mm deep, 2.5‐cm spacing), and fraze mowing at 0.6‐, 1.2‐, and 2.5‐cm depths. Response variables included percentage cover, germination rating, surface hardness, and percentage cover the following spring and summer. Results showed no differences between preplant treatments for germination and percentage cover the following year. However, the fraze mowing treatments resulted in reduced percentage cover for 2 to 3 wk after treatment (WAT) compared with vertical mowing and the untreated control. By 3 WAT, the overseed had established and all plots had >90% cover. Surface hardness was only slightly affected by preplant treatment at just one location, and results were not consistent.